Kepribadian dalam Al-Qur’an: Analisis Nilai-Nilai Qalb dalam Membentuk Pribadi Ideal - Anggi Maulana; Kerwanto Kerwanto; Nurbaiti Nurbaiti (Ar-Rasikhin : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study explores the concept of the ideal personality in the perspective of the Qur’an as a response to the modern human personality crisis, which remains unresolved through Western theories. Psychoanalysis (Freud), behaviorism (Skinner), humanism (Maslow), and neurological approaches (Damasio, MacLean) have contributed to psychology and education but fall short in addressing the spiritual and moral dimensions of personality. In Islamic psychology, al-Ghazali and Ibn Qayyim emphasize that the nafs constitutes the core of personality, which must be viewed integrally alongside the qalb, intellect, and spirit. The Qur’an presents diverse typologies of personality shaped by the condition of the qalb, such as nafs ammārah, lawwāmah, and muṭma’innah, as well as categories of believers, disbelievers, and hypocrites. Within this framework, qalbun salīm emerges as the foundation of the ideal personality— a heart purified from vain desires and doubts, guiding the intellect and nafs toward spiritual balance and moral integrity. Employing a thematic (mawḍū‘ī) exegesis approach through library research, this study finds that the Qur’an offers an integral, theocentric, and transcendental paradigm of personality. This paradigm provides a constructive alternative to contemporary personality crises by positioning the heart and human nature (fiṭrah) as the central basis of personality development.